Use of GeneXpert Mycobacterium tuberculosis/rifampicin for rapid detection of rifampicin resistant Mycobacterium tuberculosis strains of clinically suspected multi-drug resistance tuberculosis cases - Guenaoui, Kheira (Ann Transl Med, 2016)
BACKGROUND: Multi-drug resistance (MDR) TB is defined as tuberculosis (TB) disease caused by a strain of Mycobacterium tuberculosis (MTB) that was resistant to at least isoniazid and rifampicin (RIF). Emerging Multidrug-Resistant TB is one of the major concerns of health policy and rapid detection of M. tuberculosis and detection of RIF resistance in infected patients are essential for disease management. The aim of this study was to evaluate patterns of RIF resistance in cases of sputum positive pulmonary TB by using GeneXpert MTB/RIF and comparing between phenotypic and genotypic testing of RIF resistance in MTB strains of clinically suspected MDR-TB isolated cases in western Algeria. METHODS: In this study 50 sputum positive cases of pulmonary TB who were potential MDR suspect were included. Their sputum samples were collected and subjected to sputum smear microscopy, culture and conventional MTB/RIF test followed by GeneXpert MTB/RIF assay. RESULTS: Of total 50 cases included in this study, MTB was detected in all patients (100%) by GeneXpert MTB/RIF. However, RIF’s resistance was detected in only 21 cases (42%) by GeneXpert MTB/RIF. All RIF resistant strains detected by GeneXpert MTB/RIF were phenotypically confirmed as MDR strains. 42.85% of cases were retreatment failure cases, retreatment cases smear positive at 4 months were 23.82%. While 19.05% of cases were retreatment cases smear positive at diagnosis, and 14.28% patient had history of contact with MDR-TB. Sensitivity, specificity, positive predictive value and negative predictive value of Xpert MTB/RIF to detect RIF resistance in comparison to conventional phenotypic drug susceptibility technique were found equal to the rates of 100%, 100%, 100% and 100%, respectively. CONCLUSIONS: GeneXpert MTB/RIF assay is efficient and reliable technique for the rapid diagnostic of TB. It’s simplicity, high sensitivity and specificity for RIF resistance detection make this technique a very attractive tool for diagnostic of MTB and RIF resistance in MDR cases.